Synthesis and characterization of PEBAX 1657 and hierarchical Linde Type-T (h-LTT) zeolite for the fabrication of hybrid membranes - Tengku Hassan, T.N.A. (Elsevier Ltd, 2020)
Zeolites embark as a promising inorganic filler for hybrid membrane fabrication. However, small size of microporous structure and long diffusion path length of zeolites may restrict gas transport across the pore channel. Thus, hierarchical zeolites have been introduced as a prominent approach to overcome the diffusion limitation via the presence of bimodal porous structures of micropore and mesopore. In the present work, pristine PEBAX 1657 and hierarchical Linde Type-T (h-LTT) zeolite particles were prepared for the fabrication of hybrid membrane in CO2/CH4separation. The resultant particles and membrane were characterized using field emission scanning electron microscopy (FESEM), Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD) and thermogravimetric analysis (TGA). FESEM analysis demonstrates the dense symmetric structure of pristine PEBAX 1657 membrane and column-shape morphology of h-LTT zeolite particles with average particle size of 1.38 µm. On the other hand, pristine PEBAX 1657 membrane also exhibit a semi-crystalline structure and a thermal stability up to 370 °C. In addition, the permeation properties of the pristine membrane for single gas was also tested. The pristine membrane demonstrates CO2permeability and CO2/CH4selectivity of 74.27 Barrer and 14.26, respectively. © 2020 Elsevier Ltd. All rights reserved.